Improving Adolescent Nutrition by Providing Iron Supplements at Al-Hikam Islamic Boarding School, Bangkalan: Improving adolescent nutrition by providing iron supplements at Al-Hikam Islamic Boarding School, Bangkalan - zata, fariska; Junaedi, M. Dwinanda; Hidayat; Sabila, Danisa Nur; Rodhiyana, Rosda (Journal of Health Community Service, 2025)
Background: Adolescent girls are vulnerable to nutritional problems, especially anemia, which can be caused by a lack of iron intake during menstruation. Improving the nutritional status of adolescents can be done through the provision of iron supplements. This program aims to increase the awareness and knowledge of female students about the importance of nutritional health and the risk of anemia due to iron deficiency. Methods: The implementation of this program used the Community-based Participatory Research (CBPR) method involving 37 female students. The activity began with the distribution of pre-test questionnaires to assess initial knowledge about nutrition and anemia. The material presented included anatomy and physiology of female reproductive organs, health risks related to anemia, and the importance of iron supplementation. After the education, participants were asked to fill out a post-test questionnaire to evaluate knowledge improvement. Results and Discussion: The results of the activity showed a significant increase in knowledge. In the pre-test, 54.05% of participants had good knowledge, while after counseling, this percentage increased to 91.89%. There were no participants who had poor knowledge after the counseling activity. This shows that the educational program on iron supplementation is effective in increasing the understanding of santriwati regarding the importance of nutrition in preparing for a healthy pregnancy in the future. Conclusion: This activity has a positive impact on improving the nutrition and health knowledge of adolescents at Pondok Pesantren Al Hikam. Similar efforts are expected to be carried out on an ongoing basis to prevent anemia problems and support reproductive health in adolescent girls in the pesantren environment.